Aporia and Its Narrative Structure in the Novel The Unnamable by Samuel Beckett - Abashidze, Helen Leli (Caucasus Journal of Social Sciences, 2013)
The article deals with the scientific framework of the less widespread stylistic device aporia, focusing on its definition, peculiarities, function and effect caused by it. Aporia as a stylistic-phonetic device has gained a great power and a new mode of expression in the timeless example of 20th century prose – by Samuel Becket. The Unnamable is a stream-of-consciousness novel, but not like Joyce’s Ulysses, where the sights, sounds, smells and human bustle of Dublin are evoked for us, in vivid specificity, through the sense- impressions, thoughts and memories of the chief characters. All we have is a narrative voice talking to itself, or transcribing its own thoughts as they occur, longing for extinction and silence, but condemned to go on narrating, though it has no story worth telling, and is certain of nothing, not even of its own position in space and time. Beckett was a deconstructionist avant la letttre. “ I seem to speak, it is not I, about me, it is not about me ”Aporia is a favorite trope of deconstructionist critics, because it epitomizes the way in which all texts undermine their own claims to a determinate meaning; but the narrator’s later admission, “that I say aporia without knowing what it means”, is a trumping of aporia. What is extraordinary is that this bleakly pessimistic and skeptical text is not deeply depressing to read, but on the contrary funny, affecting, and in a surprising way affirmative of the survival of the human spirit in extremis. Its famous last words are: “you must go on, I can’t go on, I’ll go on”